Functional Mapping of Phenotypic Plasticity of Staphylococcus aureus Under Vancomycin Pressure - Yang, Dengcheng; Zheng, Xuyang; Jiang, Libo; Ye, Meixia; He, Xiaoqing; Jin, Yi; Wu, Rongling (Frontiers in Microbiology, 2021)
Phenotypic plasticity is the exhibition of various phenotypic traits produced by a single genotype in response to environmental changes, enabling organisms to adapt to environmental changes by maintaining growth and reproduction. Functional mapping and bivariate functional mapping can be applied to assess the relationships between multiple phenotypes and genotypes during the dynamic development of bacteria. In this study, 99 Staphylococcus aureus strains were cultured in increasing concentrations of vancomycin (0, 2, 4 and 6 μg/mL), and their growth was measured. The developmental phenotypes of the vancomycin-treated S. aureus strains were assessed by plotting logistic growth curves. The growth curve was used as a multivariate normal distribution to construct the likelihood function to realize functional mapping and bivariate functional mapping. Through functional mapping and bivariate curve analysis, 78 significant single nucleotide polymorphisms were identified following analysis of the whole growth and development process, and seven genes key to phenotypic plasticity under the pressure of vancomycin were identified. The genes SAOUHSC_00020 (walR), SAOUHSC_00176, SAOUHSC_00544 (sdrC), SAOUHSC_02998, SAOUHSC_00025, SAOUHSC_00169 and SAOUHSC_02023 genes were found to play important roles in the regulation of phenotypic plasticity in S. aureus subjected to antibiotic pressure. Our study provides dynamic gene mapping techniques for dissecting the phenotypic plasticity mechanisms of S. aureus under vancomycin pressure, emphasizing the feasibility and potential of functional mapping in the study of bacterial phenotypic plasticity.